2021
DOI: 10.1017/s0033291721004128
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological differences between treatment-resistant and treatment-responsive schizophrenia: a meta-analysis

Abstract: Antipsychotic treatment resistance affects up to a third of individuals with schizophrenia. Of those affected, 70–84% are reported to be treatment resistant from the outset. This raises the possibility that the neurobiological mechanisms of treatment resistance emerge before the onset of psychosis and have a neurodevelopmental origin. Neuropsychological investigations can offer important insights into the nature, origin and pathophysiology of treatment-resistant schizophrenia (TRS), but methodological limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 84 publications
1
17
0
1
Order By: Relevance
“…We found no evidence that the relationship between glutamate and verbal memory differed between good and poor antipsychotic responders. Whilst both worse verbal cognition and higher ACC glutamate may be associated with treatment resistance 66 68 , the lack of interaction suggests that there is no qualitative difference in the relationship between glutamate and cognition between antipsychotic response groups, at least within the ranges of antipsychotic response, glutamate, and cognitive function measured in the current study. Alternatively, it is possible that the lack of group difference in the relationship between glutamate and cognition may be due to the relative similarity in cognitive function between good and poor antipsychotic responders in our sample 55 .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We found no evidence that the relationship between glutamate and verbal memory differed between good and poor antipsychotic responders. Whilst both worse verbal cognition and higher ACC glutamate may be associated with treatment resistance 66 68 , the lack of interaction suggests that there is no qualitative difference in the relationship between glutamate and cognition between antipsychotic response groups, at least within the ranges of antipsychotic response, glutamate, and cognitive function measured in the current study. Alternatively, it is possible that the lack of group difference in the relationship between glutamate and cognition may be due to the relative similarity in cognitive function between good and poor antipsychotic responders in our sample 55 .…”
Section: Discussionmentioning
confidence: 56%
“…Impaired verbal memory function is also evident in the clinical high-risk phase of psychosis and is more severe in high-risk subjects who later progress to psychosis 64 , 65 . A recent meta-analysis found that verbal memory impairments are more apparent in treatment-resistant compared to treatment-responsive schizophrenia 66 , and prospective investigation suggests this group difference is detectable from the first episode of psychosis 67 . However, cognitive performance did not differ between the good and poor antipsychotic response groups in our cohort 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application would also require further optimization and standardization of 1 H-MRS data acquisition, analysis and testretest reliability across scanner manufacturers. Gains in accuracy could also potentially be achieved by combining glutamate measures with other predictors of response, such as resting state activity [60], brain volumes [9], perfusion [61], striatal dopamine synthesis capacity [62], cognitive performance [63] and clinical or demographic predictors [41,42,64].…”
Section: Discussionmentioning
confidence: 99%
“…This study even found that the treatment-resistant cases differed from treatment-responsive cases in deficits in the domain of memory and learning and also language function. In general, language and verbal intelligence deficits are not the most differentiating finding in schizophrenia compared with healthy controls; however, the deficit in this domain was the most distinguishing feature between treatment-resistant and treatment-responsive schizophrenia on neuropsychological testing ( 47 ). Neurolinguistic research may be an important area of work even in a globalized world where language and culture are continually adapting to the migration of people.…”
Section: Understanding Treatment-resistant Schizophreniamentioning
confidence: 99%